2019
DOI: 10.3390/en12163132
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Tin Alloys for the Electrocatalytic Reduction of CO2 in an Imidazolium-Based Non-Aqueous Electrolyte

Abstract: The ability to synthesize value-added chemicals directly from CO2 will be an important technological advancement for future generations. Using solar energy to drive thermodynamically uphill electrochemical reactions allows for near carbon-neutral processes that can convert CO2 into energy-rich carbon-based fuels. Here, we report on the use of inexpensive CuSn alloys to convert CO2 into CO in an acetonitrile/imidazolium-based electrolyte. Synergistic interactions between the CuSn catalyst and the imidazolium ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…The IL-based electrolyte can also adsorb and stabilize CO 2 ⋅– , which is favorable for CO 2 reduction. CuSn alloys can also efficiently reduce CO 2 in an IL-based electrolyte at low overpotential 81 due to the synergistic effect between two metals.
Figure 7 The Results of Different Cu-Based Catalysts with Various IL-Based Electrolytes (A and B) X-ray photoelectron spectroscopy of (A) Cu 2p and (B) Pd 3d levels of catalysts.
…”
Section: Main Textmentioning
confidence: 99%
“…The IL-based electrolyte can also adsorb and stabilize CO 2 ⋅– , which is favorable for CO 2 reduction. CuSn alloys can also efficiently reduce CO 2 in an IL-based electrolyte at low overpotential 81 due to the synergistic effect between two metals.
Figure 7 The Results of Different Cu-Based Catalysts with Various IL-Based Electrolytes (A and B) X-ray photoelectron spectroscopy of (A) Cu 2p and (B) Pd 3d levels of catalysts.
…”
Section: Main Textmentioning
confidence: 99%
“…For instance, He and co‐workers published a detailed review about bimetallic mixtures and the studies showed an improvement in the performance for the CO 2 reduction due to the use of these systems [19] . More recently, works have continued this topic using Sn−Pb−Sb alloy foil, [20,21] nanoporous Cu−Ag alloys, [22] Cu−Sn alloys, [23–26] Sn−Sb alloys, [27] Cu−Sb alloys, [28] Cu−Bi amorphous bimetallic electrocatalysts, [29] or In−Sn alloy core‐shell nanoparticles [30]…”
Section: Introductionmentioning
confidence: 99%
“…For instance, He and co-workers published a detailed review about bimetallic mixtures and the studies showed an improvement in the performance for the CO 2 reduction due to the use of these systems. [19] More recently, works have continued this topic using SnÀ PbÀ Sb alloy foil, [20,21] nanoporous CuÀ Ag alloys, [22] CuÀ Sn alloys, [23][24][25][26] SnÀ Sb alloys, [27] CuÀ Sb alloys, [28] CuÀ Bi amorphous bimetallic electrocatalysts, [29] or InÀ Sn alloy core-shell nanoparticles. [30] Tin and bismuth are the most studied metals for the CO 2 RR towards formic acid/formate and, with respect to them, recent bimetallic studies have revealed that the Bi presence improves the performance of Sn catalysts, [31,32] although pure Bi catalysts outperform those combining Sn and Bi.…”
Section: Introductionmentioning
confidence: 99%
“…39,40 The formation of such species has been implicated in recent studies of CO 2 RR over CuSn alloys in the presence of [BMIM] + electrolytes. 26 It is possible that the adsorption of the imidazolium-based organics serves to mitigate the inherent activity of the RM electrode and that the imidazolium and deprotonated carbene species may show a higher affinity (or binding strength) for some of the RM constituent elements than others. For example, although the extent of imidazolium/carbene adsorption has not been previously determined for electrodeposited Bi, Sn, or Pb monometallic thin films, it is possible that such species absorb more strongly to Pb.…”
Section: Acs Applied Energy Materialsmentioning
confidence: 99%
“…23−25 It has also been demonstrated that CuSn alloys can promote CO 2 RR in the presence of [BMIM] + -based ionic liquids under nonaqueous conditions. 26 In this study, we build on recent work in our lab devoted to electrochemical reduction of CO 2 over post-transition metals in the presence of [BMIM] + -based electrolytes. Since prior work has demonstrated that in the presence of [Im] + electrolytes, Bi, Sn, and Pb can all promote production of CO from CO 2 , we have now worked to benchmark each of these materials under a common set of electrolyte conditions to holistically compare their CO 2 RR selectivities and activities.…”
Section: ■ Introductionmentioning
confidence: 99%